Digital Transformation in respect of Political Psychology: Antalya Diplomacy Forum - KAPLAN, Emine (Cyberpolitik Journal, 2021)
Recent developments in communication technologies have been efficient on every areas as well as diplomacy. The environment of diplomacy and also means of it has changed swiftly along with the turn of digital era. It is an admitted fact that the psychological states of diplomatists have an effect upon the results of negotiations. In parallel with digital transformation of diplomacy, probable outcomes of digital desks have been an object of interest in respect to the political psychology. In this paper, the diplomatic negotiations are analyzed in terms of political psychology. While analyzing the digital diplomacy in respect of political psychology, the method of in-depth interview in addition to the literature view. Following these searches, it is concluded that the digital negotiations are have a negative effect on the diplomatic debates.